MAPK and PI3K activities are required for leptin stimulation of protein synthesis in human trophoblastic cells - Pérez-Pérez, Antonio (2010)
Leptin, the LEP gene product, is produced in placenta where it has been found to be an important autocrine signal for trophoblastic growth during pregnancy. Thus, we have recently described the antiapoptotic and trophic effect of leptin on choriocarcinoma cell line JEG-3, stimulating DNA and protein synthesis. We have also demonstrated the presence of leptin receptor and leptin signaling in normal human trophoblastic cells, activating JAK-STAT, PI3K and MAPK pathways. In the present work we have employed dominant negative forms of MAPK and PKB constructs to find out the signaling pathways that specifically mediates the effect of leptin on protein synthesis. As previously shown, leptin stimulates protein synthesis as assessed by 3H-leucine incorporation. However, both dominant negative forms of MAPK and PKB inhibited protein synthesis in JEG-3 choriocarcinoma cells. The inhibition of PKB and MAPK activity by transfection with the dominant negative kinases prevented the leptin stimulation of p70 S6K, which is known to be an important kinase in the regulation of protein synthesis. Moreover, leptin stimulation of phosphorylation of EIF4EBP1 and EIF4E, which allows the initiation of translation was also prevented by MAPK and PI3K dominant negative constructs. Therefore, these results demonstrate that both PI3K and MAPK are necessary to observe the effect of leptin signaling that mediates protein synthesis in choriocarcinoma cells JEG-3. © 2010 Elsevier Inc. All rights reserved.